Traduire pour quoi faire ? Arguments justifiant l’utilité de la traduction dans le prologue de l’Ysopete historiado - Sophie Coussemacker (E-Spania)
The paper examines the arguments put forward to justify the translation of the fables into the vernacular language in the prologue to the Castilian Ysopete historiado, which is present in several editions (1482 to 1496). It is in fact a reworking of the prologue invented by the German translator of esopic fables, Heinrich Steinhöwel. To justify these translations, the latter refers to the long lineage of translations of fables from Greek to Latin, then to vernacular languages. He also adds a justification by the readership: fables should not be reserved only for literate princes, but should be used to educate everyone. This justification is part of a debate that animated the humanist milieu, particularly in Italy, which was not in itself hostile to fables, but to their "popular" vernacular versions.